Palladium nanoparticles supported on magnesium hydroxide fluorides: a selective catalyst for olefin hydrogenation - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (ChemCatChem, 2014)
A one-pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol-gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol-gel method led to high surface area (>135 m(2)g(-1)), mesoporous catalysts (pore volume=0.19-0.23 cm(3)g(-1), pore diameter=3-5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47%) was obtained with 1 wt% palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100% conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; magnesium fluorides; Palladium

Epoxide ring-opening reaction by using sol-gel-synthesized palladium supported on a strontium hydroxyl fluoride catalyst - Acham, Vaibhav R.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (Comptes Rendus Chimie, 2016)
Palladium supported on a strontium hydroxyl fluoride catalyst was synthesized by a one-pot fluorolytic sol-gel method. The prepared catalyst was characterized by various physicochemical techniques. The sol-gel method has led to the formation of a high surface area (57 m(2)g(-1)), mesoporous (pore diameter = 13.0 nm) catalyst with uniform dispersion of Pd nanoparticles of size similar to 7 nm on the surface of strontium hydroxyl fluoride. The catalyst was used for epoxide alcoholysis, and 100% conversion was obtained with 96% selectivity for beta-alkoxy alcohols under mild conditions: The catalyst could be recycled for up to three catalytic cycles without any appreciable decrease in conversion and selectivity, indicating the stability of the catalyst under the reaction conditions. Further, the mechanism of alcoholysis was proposed on the basis of the physicochemical characteristics of the catalyst and on the basis of the products formed during the catalytic reaction. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

Palladium supported on fluorinated magnesium hydroxide: an efficient catalyst for hydrogenation under ambient conditions - Kokane, Reshma S.; Acham, Vaibhav R.; Kulal, Atul B.; Kemnitz, Erhard; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistryselect, 2017)
In this study palladium supported on fluorinated magnesium hydroxide (Pd-MgF2-x(OH)(x)) was synthesized by fluorination of magnesium hydroxide using aqueous HF as fluorinating agent. The Mg(OH)(2) dissolves in HF and precipitates as magnesium hydroxide fluoride. The Pd precursor was added in the same pot during precipitation of MgF2-x(OH)(x). The final catalyst after drying at 250 degrees C has shown very high efficiency for hydrogenation of styrene and range of nitro aromatics at room temperature and atmospheric pressure. Hydrogenation of styrene has led to 37% conversion with 100% selectivity for hydrogenation of double bond after 3 h. The catalyst was successfully recycled for styrene hydrogenation without appreciable loss in the activity. Further hydrogenation of nitro-aromatics was achieved with 99% conversion and 100% aniline selectivity at room temperature and atmospheric pressure. The turnover number of similar to 21774 was obtained for nitrobenzene hydrogenation. The catalyst has shown mesoporous nature (pore volume 0.25 cc/g, pore diameter 4.8 nm) with very high surface area of 106 m(2)/g. The palladium particle size was found to be in the range of 10-11 nm. Acidity measurements by FTIR of adsorbed pyridine revealed presence of Lewis acidic sites with moderate acidity. Mechanistic studies using in-situ FTIR analysis for nitrobenzene hydrogenation revealed activation of nitrobenzene on the Lewis acid sites of the support whereas activation of hydrogen by heterolytic cleavage on Pd center.

Palladium supported on magnesium hydroxyl fluoride: an effective acid catalyst for the hydrogenation of imines and N-heterocycles - Kokane, Reshma; Corre, Yann; Kemnitz, Erhard; Dongare, Mohan K.; Agbossou-Niedercorn, Francine; Michon, Christophe; Umbarkar, Shubhangi B. (New Journal of Chemistry, 2021)
Palladium catalysts supported on acidic fluorinated magnesium hydroxide Pd/MgF2-x(OH)(x) were prepared through precipitation or impregnation methods. Applications to the hydrogenation of various aldimines and ketimines resulted in good catalytic activities at mild temperatures using one atmosphere of hydrogen. Quinolines, pyridines and other N-heterocycles were successfully hydrogenated at higher temperature and hydrogen pressure using low palladium loadings and without the use of any acid additive. Such reactivity trend confirmed the positive effect of the Bronsted and Lewis acid sites from the fluorinated magnesium hydroxide support resulting in the effective pre-activation of N-heterocycle substrates and therefore in the good catalytic activity of the palladium nanoparticles during the hydrogenations. As demonstrated in the hydrogenation of imines, the catalyst was recycled up to 10 times without either loss of activity or palladium leaching.